The Value of Systematic Reviews - Neilson, JP (Nepal Journal of Obstetrics and Gynaecology, 2016)
In 2013, a workshop was held in Kathmandu that explored systematic reviews – what they are, how they are developed, how they are used in evidencebased clinical guidelines, and how they can inform the clinical research agenda. The workshop was funded by the Gates Foundation through FIGO, and organised by the Nepal Society of Obstetricians and Gynaecologists.